020 Human exercise induced circulating progenitor cell mobilisation is nitric oxide dependent and is blunted in South Asian men. (22nd September 2015) - Cubbon, R M; Murgatroyd, S R; Ferguson, C; Bowen, T S; Rakobowchuk, M; Baliga, V; Cannon, D; Rajwani, A; Abbas, A; Kahn, M; Birch, K M; Porter, K E; et al.
Abstract : Background: Circulating progenitor cells (CPCs) have emerged as potential mediators of vascular repair. In experimental models CPC mobilisation is critically dependent on nitric oxide (NO). South Asian ethnicity is associated with reduced CPCs; we assessed CPC mobilisation in response to exercise in Asian men and examined the role of NO in CPC mobilisation per se. Methods: In 15 healthy white European men and 15 matched South Asian men, CPC mobilisation (relative % increase from pre- to post-exercise) was assessed during moderate intensity exercise using flow cytometry. Three subsets of CPCs were studied (CD34+/KDR+, CD133+/CD34+/KDR+ or CD34+/CD45−) and were expressed as a % of circulating lymphocytes). Brachial artery flow mediated vasodilatation (FMD) was used to assess NO bioavailability. To determine the role of NO in CPC mobilisation, identical exercise studies were performed during intravenous separate infusions of saline, the NO synthase inhibitor L-NMMA, and norepinephrine. Results: Groups were well matched for age, blood pressure, indices of obesity and circulating lipids; however the South Asian group exhibited insulin resistance as measured by the HOMA-IR score (1.3±0.2 vs 0.8±0.1; p=0.047). FMD (5.8±0.4% vs 7.9±0.5%; p=0.002) and basal CPC numbers (CD34+/KDR+: 0.030% vs 0.046%, p=0.05; CD133+/CD34+/KDR+: 0.008% vs 0.014%, p=0.026; CD34+/CD45−: 0.011% vs 0.018%, p=0.044) were lower in the South Asian group. CPC mobilisation (CD34+/KDR+ 53.2% vs 85.4%, p=0.001; CD133+/CD34+/KDR+ 48.4% vs 73.9%, p=0.05; CD34+/CD45− 49.3% vs 78.4, p=0.006) was blunted in the South Asian group. CPC mobilisation correlated with FMD and L-NMMA significantly reduced exercise induced CPC mobilisation (CD34+/KDR+ −3.3% vs 68.4%; CD133+/CD34+/KDR+ 0.7% vs 71.4%; CD34+/CD45− −30.5% vs 77.8%; all p<0.001). Conclusions: In humans NO is critical for CPC mobilisation in response to exercise. Reduced NO bioavailability may contribute to imbalance between vascular damage and repair mechanisms in South Asian men. This project was supported by the British Heart Foundation.